Maximal power at different percentages of one repetition maximum: influence of resistance and gender - Thomas, G. A.; Kraemer, W. J.; Spiering, B. A.; Volek, J. S.; Anderson, J. M. (The Journal of Strength and Conditioning Research, 2007)
National Collegiate Athletic Association Division I athletes were tested to determine the load at which maximal mechanical output is achieved. Athletes performed power testing at 30, 40, 50, 60, and 70% of individual 1 repetition maximum (1RM) in the squat jump, bench press, and hang pull exercises. Additionally, hang pull power testing was performed using free-form (i.e., barbell) and fixed-form (i.e., Smith machine) techniques. There were differences between genders in optimal power output during the squat jump (30-40% of 1RM for men; 30-50% of 1RM for women) and bench throw (30% of 1RM for men; 30-50% of 1RM for women) exercises. There were no gender or form interactions during the hang pull exercise; maximal power output during the hang pull occurred at 30-60% of 1RM. In conclusion, these results indicate that (a) gender differences exist in the load at which maximal power output occurs during the squat jump and bench throw; and (b) although no gender or form interactions occurred during the hang pull exercise, greater power could be generated during fixed-form exercise. In general, 30% of 1RM will elicit peak power outputs for both genders and all exercises used in this study, allowing this standard percentage to be used as a starting point in order to train maximal mechanical power output capabilities in these lifts in strength trained athletes.